Laporan kasus: Infeksi toxocara canis pada anjing domestik (Canis familiaris) - Usma Aulia; Anna Zukiaturrahmah; Juliadi Ramadhan; Ario Ridho Gelagar (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
Dogs are one of the human pets that are often affected by parasitic infections, both endoparasites (helminths and protozoa) and ectoparasites (fleas, ticks, fleas, and mites). Endoparasites that are often reported are helminth cases, namely Ancylostomiasis, Toxocariasis, Dipylidiasis, Trichuriasis and Nekatoriasis. Toxocara canis is one of the most widespread public health and economically important zoonotic parasitic infections humans share with dogs. Meanwhile, the ectoparasites, especially fleas, that are often encountered are Ctenocephalides canis. The method used to detect the presence of worms is native, centrifugation, and floating feces examination and Mc Master Chamber calculation to determine the severity of the worm infection. In this case, blood tests were also carried out. Flea examination is carried out by identifying ectoparasite wet preparations. The results of a floating stool examination revealed Toxocara canis worm eggs. The ectoparasite obtained after laboratory examination was the flea Ctenocephalides canis. The treatment used to treat helminth disease is by administering worm medicine, while for flea disease it can be done by anti-flea injection. Prevention can be done by administering worm medicine regularly and keeping the dog's cage and environment clean.